Maternal Feeding Styles and Child Appetitive Traits: Direction of Effects in Hispanic Families With Low Incomes - Maria A. Papaioannou; Nilda Micheli; Thomas G. Power; Teresia M. O'Connor; Jennifer Orlet Fisher; Sheryl O. Hughes (Frontiers Media S.A., 2022)
Feeding styles of parents have been associated with dietary quality/intake and weight outcomes; however, much of the research to date has been cross sectional and the direction of influence unclear. This prospective longitudinal study evaluated the direction of effects between feeding styles and child appetitive traits over time in a sample of 129 Hispanic parent/child dyads that participated in a larger study. Data analyzed for the current study were collected when the children were 4-5 years old and again at ages 7-9 years. Parents (all mothers) reported on their feeding styles and children's appetitive traits using well-established questionnaires. Cross-lagged panel analyses were used to examine the direction of effects. Fully adjusted models revealed that a number of children's appetitive traits at baseline predicted later feeding styles. A bi-directional relationship was found between authoritarian feeding and satiety responsiveness such that higher satiety responsiveness was associated with authoritarian feeding and vice versa. Lower satiety responsiveness was associated with indulgent feeding, whereas higher food responsiveness was associated with authoritarian feeding. Results show preliminary evidence that children's appetitive traits may shape mothers' approach to child feeding. There is also preliminary support for the protective role of an authoritarian feeding style in the self-regulatory processes around child appetitive traits among this population of Hispanic families with low-income levels. These results warrant continued research given that other studies have shown beneficial outcomes for authoritarian feeding among ethnically diverse families with low incomes.